Promoting Health Literacy Among Pregnant Women to Prevent Fine Particulate Matter (PM2.5) Exposure: A Midwife’s Role - Puektes, Supa; Techawathakul, Suchada (Thai Red Cross Nursing Journal, 2023)
The prevalence of PM2.5 particulate matter has been increasing in Thailand. Inhalation of PM2.5 can cause obstetric complications such as pregnancy induced hypertension (PIH), gestational diabetes mellitus (GDM), preterm labor, and a low birth weight for the child. Health literacy encompasses the cognitive and social skills that determine an individual’s motivation and self-care ability. Therefore, midwives should play a vital role promoting health literacy among pregnant women; through demonstrating abilities such as access, understanding, communication, self-management, decision-making and media literacy, midwives can help pregnant women reduce their PM2.5 exposure to improve the health of preg